Sintesis dan karakterisasi silika tersulfatasi dari sekam padi - Idra Herlina; Edwin Rizki Safitra (Jurnal Rekayasa Proses, 2018)
In this work, sulphated silica (SiO2/SO3-H+) has been synthesized from rice husk through sol-gel method. Characterization with IR spectrophotometers showed similar peak between silica and sulphated silica. Silica typical bands consisting of strain O-H, bending water molecules, and asymmetric vibrations of silica atoms present in the siloxane appear at the peak of the analysis showing that silica synthesis of rice husk has been successfully performed. The modification of silica with sulphuric acid was not confirmed by IR spectrophotometers because the S-OH strain of sulphate ions overlaps with asymmetric vibrations of silica atoms present in siloxanes. The resulting sulphated silica was used as a catalyst in the esterification reaction of free fatty acid in a crude palm oil pond (Pond CPO). Pond CPO is a CPO that is bound to palm oil mill waste water. Pond CPO has free fatty acid content (FFA) between 40 to 70%. High levels of FFA CPO can be derived through esterification reactions with the help of SiO2/SO3-H+ catalyst. In this study, SiO2/SO3-H+ catalyst concentrations were varied i.e. 1, 3, and 5% (w/w). From the research result, the best catalyst performance was obtained at 5% concentration with the ability to decrease the FFA level by 49.70%.